Isolated rupture of duodenum following blunt trauma abdomen: report of a case of avulsion of pylorus - Balasubramanian, Gopal; Vijayakumar, Chellappa; Anbarasu, Inbasekaran; Sudharsanan, Sundaramurthi; Raj Kumar, Nagarajan; Baskaran, Dhanapal (International Surgery Journal, 2017)
Isolated duodenal injury following blunt trauma do not occur often. A patient with complete damage to the duodenum presents a challenge to the surgeons. The choice of procedure must be tailored to the nature of the defect and the amount of tissue lost. A 19-years-old male presented with features of bowel perforation following blunt injury abdomen. After initial conservative management, the patient was taken up for laparotomy. A complete transection of duodenum with avulsion of pylorus was found. Primary closure of duodenum and pylorus with omental patch support was done. The patient made an uneventful recovery. The choice of procedure may vary and it depends on the patient condition and surgeon capability. Primary closure of disturbed ends without any gastric diversion procedure is the excellent choice in a young patient with blunt injury without major intraoperative contamination. Primary closure is also a challenging procedure compared to other natural tailoring techniques.